2010
DOI: 10.1021/jp1071764
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Dependence of Electronic Coupling Across Peptide Bonds: A Ramachandran Map

Abstract: Electronic coupling across peptide bonds has been determined throughout the peptide bond conformational space. Using the side chains of tyrosine (Tyr) and tryptophan (Trp) as donors (D) and acceptors (A), respectively, a plot of the electronic coupling matrix element H DA versus (ϕ,ψ) torsional angles has been constructed for Trp-peptide-Tyr molecules. The H DA values were obtained using the generalized Mulliken−Hush approach with electronic transition energies, permanent and transition dipole parameters deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…40 More support for the importance of peptide chain length and conformations comes from the work of Isied and coworkers, who demonstrated that distances between donors and acceptors and torsional angles within peptides are critical. 41…”
Section: Effect Of Peptide Chain Length -Hopping Versus Tunnelingmentioning
confidence: 99%
“…40 More support for the importance of peptide chain length and conformations comes from the work of Isied and coworkers, who demonstrated that distances between donors and acceptors and torsional angles within peptides are critical. 41…”
Section: Effect Of Peptide Chain Length -Hopping Versus Tunnelingmentioning
confidence: 99%
“…The results emphasized the impact of structural fluctuations on the electronic coupling and hence also on protein electron transfer, being well established in the literature. [115][116][117][118][119][120][121][122] Over the past few years, there has been evidence supporting the idea that many inter-protein ET complexes are highly transient as a characteristic consequence of their biological function. These complexes are optimized by evolution to react fast, not to achieve high specificity.…”
Section: Protein Dynamics and Transient Et Complexesmentioning
confidence: 99%
“…5 During superexchange, the amino acids mediate ET and do not undergo a change in their redox states while during hopping, certain amino acids are reversibly oxidized or reduced and serve as relay stations (stepping stones) for the ET process. Important parameters that influence ET mechanisms are peptide conformations, 6,7 peptide flexibility, 8 and redox potentials of the peptide side chains that might become stepping stones for a hopping process if their redox potentials are low enough. 5,9 Of special interest are a-and 3 10 -helices as their high dipole moments could strongly change the redox potential of the amide groups of the peptide backbone.…”
Section: Introductionmentioning
confidence: 99%
“…Recent calculations of Isied et al have shown that in a-/3 10 -helical peptides the electron coupling between the amide groups is strong. 7 In addition, H-bonds could be used as a pathway for the ET process.…”
mentioning
confidence: 99%